Sex differences in obstructive sleep apnoea - Maria R. Bonsignore; Tarja Saaresranta; Renata L. Riha (European Respiratory Review, 2019)
Obstructive sleep apnoea (OSA) and obstructive sleep apnoea/hypopnoea syndrome (OSAHS) have long been considered predominantly male-related conditions. The clinical presentation of sleep disordered breathing in females differs from males and can vary with age and physiological status, e.g. menopause and pregnancy. Overall, females appear to be more symptomatic, with lower apnoea–hypopnoea index scores compared to males. Furthermore, they appear to have more prolonged partial upper airway obstruction, and may report insomnia as a symptom of OSAHS more frequently. As a consequence of these differences in clinical presentation, females with sleep disordered breathing are often underdiagnosed and undertreated compared to males. This review is aimed at discussing the epidemiology, clinical presentation, pathophysiology and hormonal and metabolic differences in females who present with OSA/OSAHS in comparison to males.